DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION TEACHING MATERIALS BASED ON ECOLITERACY AT SMP NEGERI 3 STABAT - Raden Fadli Daulay; Masganti Sit; Mahariah Mahariah (JURNAL TARBIYAH, 2024)
This research aims to find ecoliteracy-based PAI teaching materials, which are feasible, practical and effective for use in learning. The research was conducted at SMP Negeri 3 Stabat. This research method is a development research method with the Plomp model. The research instruments used were validation sheets, observation sheets and learning outcomes tests. The research findings show: (1) ecoliteracy-based PAI teaching materials were developed starting from needs analysis, design, testing and revision. In this case, the PAI teaching materials developed contain the concept of ecoliteracy, (2) ecoliteracy-based PAI teaching materials have been tested, evaluated and revised, in this case their suitability has been validated by learning design experts, material experts and educational practitioners with an average score of 3. 30 eligible categories. Thus, the teaching material products developed are suitable for use in PAI learning, and (3) ecoliteracy-based PAI teaching materials have been implemented with a level of practicality with a score of 3.40 in the practical category and a level of effectiveness for improving student learning outcomes, with an N-Gain score 0.39 medium effectiveness category.